Transcriptional response provides insights into the effect of chronic polystyrene nanoplastic exposure on Daphnia pulex. (January 2020) - Zhang, Wenyi; Liu, Zhiquan; Tang, Shengkai; Li, Daming; Jiang, Qichen; Zhang, Tongqing
Abstract: Nanoplastic pollution is widespread and persistent across global water systems and can cause a negative effect on aquatic organisms, especially the zooplankter which is the keystone of the food chain. The present study uses RNA sequencing to assess the global change in gene expression caused by 21 days of exposure to 75 nm polystyrene (PS) nanoplastics on Daphnia pulex, a model organism for ecotoxicity . With the threshold value at P value < 0.05 and fold change >2, 244 differentially expressed genes were obtained. Combined with real-time PCR validation of several selected genes, our results indicated that a distinct expression profile of key genes, including downregulated trehalose transporter, trehalose 6-phosphate synthase/phosphatase, chitinase and cathepsin-L as well as upregulated doublesex 1 and doublesex and mab-3 related transcription factor-like protein, contributed to the toxic effects of chronic nanoplastic exposure on Daphnia, such as slowed growth, subdued reproductive ability and reproductive pattern shifting. Our study also showed that chronic exposure to nanoplastic changed the sex ratio of D. pulex neonates. By integrating the gene expression pattern in an important model organism, this study gained insight into the molecular mechanisms of the toxic effect of chronic PS nanoplastic exposure on D. pulex, which may also extend to other nanoplastics or aquatic animals. Highlights: Chronic nanoplastic exposure inhibited expression of a few key genes in D. pulex. Chronic nanoplastic exposure increased doublesex gene expression in D. pulex. Chronic nanoplastic exposure resulted in more male D. pulex neonates.